AN EXAMINATION OF THE ANTECEDENTS OF CUSTOMER SATISFACTION, BEHAVIORAL RESPONSE AND INTENTIONS AMONG RETAIL STORE FORMATS - Kumar, Pankaj (International Journal of Research -GRANTHAALAYAH, 2017)
The purpose of this study is to examine the effect of store image attributes, customer attitude and perceived value on consumers’ satisfaction, behavioral response and intentions and also, the effect of customer satisfaction on behavioral response and loyalty intentions. A structured questionnaire was successfully distributed to 600 respondents, who had made purchases from sixty retail formats operated in Delhi and Gurugram belonging to the domain of Shopping Malls, Hypermarket, Supermarket, Department Stores, Discount stores and Category Killers through systematic stratified sampling for the collection of data. Factor analysis was employed to identify the store image attributes as perceived by retail customers. Multiple regression analysis was conducted to predict customers' satisfaction, behavioral response (word of mouth communication), intention to switch, and customers’ loyalty intention from retail store image attributes, customers’ overall store attitude and perceived customer value, and to predict behavioral response and intentions from customers’ satisfaction. The results of the study showed that customers’ overall store attitude and perceived customer value are significant for all the dependent variables (customers' satisfaction, behavioral response (word of mouth communication), intention to switch, and customers’ loyalty intention), while store image is partially influencing customers’ satisfaction, behavioral response and intentions, furthermore customer satisfaction is significant predictors of customers’ behavioral response and intentions. The implications for marketers and managers have also discussed.